Pengaruh Model Project Based Learning Berbasis STEAM terhadap Hasil Belajar Peserta Didik pada Materi Transformasi Energi Kelas IV di SDN 36 Banda Aceh - Intan Syaravina; Nurmasyitah Syitah; Intan Safiah (Universitas Syiah Kuala, 2023)
ABSTRACTThe problems in this study relate to importance of choosing a learning model. A good learning model can be used to make the teaching and learning process more effective, meaningful and pleasantly. The research used to know students will get learning outcomes that can meet the KKM. And the fact of this research is teaching and learning in class is still not optimal in using learning models. Based on these problems need an update. One of the meaningful, effective, and fun learning alternatives that can be applied in developing student competencies is to use the STEAM-based project based learning model. The formulation of the problem in this study is